Fatores reguladores da dominância de Cylindrospermopsis raciborskii (Woloszynska) Seenayya & Subba-Raju no Reservatório Tabocas, Caruaru, PE - Bressan, Fernanda Affonseca (2001)
ln 1996, during haemodialysis procedure using water from Tabocas reservoir in Caruaru, Pernambuco, a massive human intoxication associated with cyanotoxins was registered. After that, a detailed monitoring program was established, including phytoplankton ecology studies. Since cyanophytes were the dominant algal group and considering their potential relevance to public health, the goals of this study were to recognise temporal and spatial patterns of distribution of these populations, mainly Cylindrospermopsis raciborskii (Woloszynska) Seenaya & Subba-Raju , and to understand the main regulating factors of its dominance. Phytoplankton and abiotic variables of water were sampled during November 1997 to October 1998, at subsurface, biweekly in three sampling stations. A vertical profile was analysed only in the station near to the dam. Considering phytoplankton composition and biomass, three periods were recognised: period I, with lower biomass and C. raciborskii dominance; period II, with similar biomass to period 1, but co-dominance of C. raciborskii and Cyanodictyon imperfectum Cronberg & Weibull; period III, with the highest biomass and dominance of C. raciborskii. Total biomass was inversely related to reservoir level and to the light. Our data support that C. raciborskii dominance was favoured by high temperature, high pH, low light and low inorganic dissolved phosphorus concentrations. Environmental constancy, defined by the persistent and strong drought, was a decisive factor to promote the long-standing cyanophytes dominance in Tabocas reservoir. According to the phytossociological approach originally developed to terrestrial vegetation and recently applied to phytoplankton, groups of species can be efficient descriptors of the environment where they live. The most representative algal assemblages in Tabocas Resevoir was S and Sn, both fitted to growth in low phosphorus concentrations and low light.